Comparison of day‐to‐day blood pressure variability in hypertensive patients with type 2 diabetes mellitus to those without diabetes: Asia BP@Home Study. Issue 3 (31st December 2019) - Chia, Yook‐Chin; Kario, Kazuomi; Tomitani, Naoko; Park, Sungha; Shin, Jinho; Turana, Yuda; Tay, Jam Chin; Buranakitjaroen, Peera; Chen, Chen‐Huan; Hoshide, Satoshi; Nailes, Jennifer; Minh, Huynh Van; et al.
Abstract: Blood pressure variability (BPV) has been shown to be independently associated with cardiovascular (CV) mortality and morbidity. Patients with type 2 diabetes mellitus (T2DM) have also been shown to have increased BPV. We aimed to compare BPV in hypertensive patients with diabetes with those without diabetes. A total of 1443 hypertensive patients measured their blood pressure (BP) twice in the morning and twice before bed at home for a week. Demographic data, history of T2DM, and anti‐hypertensive use were captured. Clinic BP was measured twice in the clinic. Control of BP was defined as clinic systolic BP (SBP) <140 mm Hg and home SBP < 135 mm Hg. BPV was based on home SBP measurements. A total of 362(25.1%) hypertensives had diabetes and 47.4% were male. Mean age was 62.3 ± 12.1 years. There was no difference in the mean clinic SBP in both groups (139.9 mm Hg vs 138.4 mm Hg P  = .188). However, the mean morning home SBP was significantly higher and control rate lower in hypertensives with diabetes than those without (132.3 ± 15 mm Hg vs 129.7 ± 14.4 mm Hg P  = .005, 39.4% vs 47.6% P  = .007), respectively. Masked uncontrolled morning hypertension was higher in those with diabetes versus those without (12.8% vs 8.4%, respectively). There was no statistically significant difference in BPV between those with and without diabetes. In summary, clinic SBP was similar in hypertensives with or without diabetes. However, control of BP based on both clinic and home SBP thresholds was poorer in hypertensives with diabetes compared to those without. Masked uncontrolled morning hypertension was higher in those with diabetes than those without. There was no difference in BPV between the two groups.